2020
DOI: 10.1007/s12601-020-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

The Accumulation of Al, As, Li, Mg, Mn, S, Si, Ti, and V in the Mussel Mytilus galloprovincialis from the Moroccan Mediterranean Coastal Areas: Trends Pertaining to Seasons and Levels

Abstract: The accumulation levels of elements (Al, As, Li, Mg, Mn, S, Si, Ti, and V) in the soft tissue of mussels (Mytilus galloprovincialis), collected monthly in 2016, from Junuary to December, from sampling sites of the mussel farming facilities installed in the coastal areas of Al Hoceima, were investigated. The studied element levels were determined by using Inductively Coupled Plasma -Optical Emission Spectrometry (ICP-OES 720-ES). Descending order of the average element concentrations in soft tissue of M. gallop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 72 publications
2
15
0
Order By: Relevance
“…The minimum values of Zn were observed in June (142.13 ± 0.83 mg/kg). In our study, the seasonal variations in the metallic pollutants observed in the mussels, with higher levels obtained in the winter season, and lower concentrations indicated in summer period have long been considered [9][10][11]. In the Al Hoceima coasts, the bioaccumulation of metallic pollutants in marine biota have been influenced by the abiotic variables and the biological states [9].…”
Section: Mytilus Galloprovincialis Soft Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum values of Zn were observed in June (142.13 ± 0.83 mg/kg). In our study, the seasonal variations in the metallic pollutants observed in the mussels, with higher levels obtained in the winter season, and lower concentrations indicated in summer period have long been considered [9][10][11]. In the Al Hoceima coasts, the bioaccumulation of metallic pollutants in marine biota have been influenced by the abiotic variables and the biological states [9].…”
Section: Mytilus Galloprovincialis Soft Tissuesmentioning
confidence: 99%
“…Lee et al [29] indicated that the phytoplankton can improve the trace elements' bioavailability for marine invertebrates. In relation to the reproductive cycle, Azizi et al [10] observed that the bioaccumulation of pollutants in Mytilus galloprovincialis was higher in winter, authors indicated that the fluctuation in heavy metal contents in bivalves depended on the variation in the animals' weight during the period of reproduction.…”
Section: Mytilus Galloprovincialis Soft Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Urbanization, agriculture and industrial developments are taking place at an accelerated rate in the coastal areas around the world [2]. These developments regenerate different sources of pollutants, which have been identified as one of the most important sources of contamination loading on the Mediterranean coast [3]. Heavy metals are a major anthropogenic contaminant in marine environment [4], because they cannot be degraded and persist in the environment; consequently, they accumulate in aquatic organisms [5].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals are defined as metallic elements that have a relatively high density compared to water and is toxic or poisonous even at low concentration [6,3]. Generally, heavy metals are toxic [11,12]. So in our study, we used bentonites clay as an adsorbent and the margin as adsorbate.…”
Section: Introductionmentioning
confidence: 99%